The quality of audiovisual translation in Turkey and the course of the production process: an empirical study on the subtitled and the dubbed versions of Will and Grace - Sayman, Aslı Süreyya. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
The present study focuses on the quality of audiovisual translations in Turkey through a case study that comprises a translation analysis and a small-sized reception study. The case study allows for a closer investigation of quality in audiovisual translations in Turkey through a textual analysis of four translations submitted by four individual translators and through a reception study which helps to establish the audience’s opinions and criticisms on AV translations performed in our country. In our study, the general tendency to solely blame the translator for the frequently encountered “poor” quality in audiovisual translations is challenged through adressing the correlation between the quality in AVT and the production process, whose main constituents are the translator’s working conditions, the recruitment criteria employed by the commisioners, on-the-job training provided by the commisioners, and finally and most importantly the existence of a reviewing/editing system. The study underscores the deficiencies of the production process of audiovisual translations in Turkey, and how these drawbacks lead to commonly observed “poor” quality in the translated versions of audiovisual products.
Keywords: Translating and interpreting in motion pictures.; Motion pictures -- Translating and interpreting.; Dubbing of motion pictures.